3(7+6x)=-15

Simple and best practice solution for 3(7+6x)=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7+6x)=-15 equation:


Simplifying
3(7 + 6x) = -15
(7 * 3 + 6x * 3) = -15
(21 + 18x) = -15

Solving
21 + 18x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 18x = -15 + -21

Combine like terms: 21 + -21 = 0
0 + 18x = -15 + -21
18x = -15 + -21

Combine like terms: -15 + -21 = -36
18x = -36

Divide each side by '18'.
x = -2

Simplifying
x = -2

See similar equations:

| -2(3x-10)=62 | | 5x-10+4x+2=180 | | 4m+6=6m-18 | | -21=3x+x+7 | | 9-4(2(-4)-1)=45 | | -41+23= | | -138=-6(2b+7) | | 3-q=-3+13 | | 10y-4=6y+12 | | r*8+5=4 | | -2=-6(x-6) | | 7-x+4x=-11 | | 2(6x+6)=48 | | N+.16=9 | | 3(1y+2)+1y=15-(1y+4) | | 6=7+k/18 | | 168=3x+3(-5x+16) | | 15x-7x=23 | | -16+11= | | 9*-5+6=-5 | | 0=3x^2-14x+8 | | -5+4R+17r=73 | | -3x-5x+6=-34 | | 16=4(-2x-6) | | -25-4(2x+5)=-61 | | 4c+5y-6z=2 | | -3x-3n=x | | -16=2(z) | | 3-9=-3-13 | | bx+4=-12 | | m+4(m+3)=28 | | 4a-2a-18=6 |

Equations solver categories